Pembuatan media pembelajaran dengan alat peraga bangun ruang menggunakan sedotan - Asrinan; Nashruddin; Suherman; Lasmi; Daffa Baswara; Aditya Eka Rumandhani; Muhammad Adika; Julfian (Jurnal Dedikasi Masyarakat, 2024)
This service aims to implement innovative learning methods in the form of learning media with space-building props using straws. This approach is implemented through community service activities to increase students' understanding of mathematical concepts, especially geometric shapes. Props made from straws were chosen to provide creative and environmentally friendly solutions in the learning process. The results of the activity show a significant increase in students' understanding of the concept of geometric shapes after participating in this activity. Students' creativity is also stimulated through the activity of making space with straws, which creates a variety of unique shapes. The use of straws not only has a positive impact on mathematical understanding but also increases students' environmental awareness. This activity also offers innovative solutions in mathematics learning that can be adopted at various levels of education. Learning media with straws provides an effective, interesting, and sustainable alternative to improve the quality of mathematics learning. This continuity of learning triggers positive changes in students' mindsets towards mathematics and the surrounding environment and builds students' creativity and independence.